Studi Lama Waktu Tinggal Partikel di Kawasan Perairan Nusa Penida, Bali - Putra, Ida Bagus Andika; Hendrawan, I Gede; Putra, I Dewa Nyoman Nurweda (Journal of Marine Research and Technology; Vol 3 No 2 (2020): AGUSTUS 2020, 2020)
Nusa Penida is a tourist destination, located on the east of Bali, which is well-known of its natural panoramic. Increasing tourism sector in Nusa Penida may have positive impacts, but it can also have negative impacts, such as an increase in the amount of waste and other pollutants, which will eventually be discharged into the waters. High concentration of pollutant can reduce water quality. The water quality in the sea can be control by the residence time, and the sea current would spread waste in the ocean. Based on these problems, it is important to conduct a research on the movement and length of particle residence in the waters of Nusa Penida, Bali. This research was carried out in January 2019, to represent the rainy season conditions, and in July 2019, to represent the dry season conditions. The residence time was calculated  using a numerical modeling method namely Finite Volume Coastal Ocean Model (FVCOM). Based on the simulation results, the residence time of particle in the dry and rainy season has a similar pattern. Areas with fast residence times are found in the eastern Nusa Penida waters, while areas with weak residence times are found in the Toyapakeh strait. Generally, Nusa Penida waters have a relatively short residence time, 1- 4 hours.